'Hm no-one says anything, did you notice?'. (1st September 2021) - Murtagh, Ged M.; Bezemer, Jeff
Abstract : Effective teamwork is a critical feature of surgical practice and is based on shared expectations and understandings between team members. These shared understandings are intimately tied to a hierarchy of expertise pertaining to role, responsibility and participation status, and it has been suggested that this can sometimes negatively impact trainees' experience of intraoperative surgical training. This paper examines this issue, exploring how surgeons and their trainees collaboratively manage decision making amidst the hierarchy of expertise. Our data set consists of audio and video recordings of surgical procedures, which are examined using conversation analysis. Our findings indicate that implicit in the interactions between consultant surgeons and trainees is the expectation that the lead surgeon is the authoritative expert and will therefore direct decision making. Trainees actively acquiesce to that order. Notwithstanding this, the analysis underscores some of the interactional practices used by surgeons and trainees which preserve, and on rare occasions, challenge that hierarchical relation. The paper concludes by considering the implications of the findings within the broader context of patient safety.